2010
DOI: 10.1007/s11064-010-0210-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GABA Receptor Binding in the Cerebral Cortex of Insulin Induced Hypoglycemic and Streptozotocin Induced Diabetic Rats

Abstract: Hypoglycemia is the major problem to blood glucose homeostasis in treatment of diabetes and is associated with severe irreversible consequences including seizures, coma and death. GABAergic inhibitory function in the cerebral cortex plays an important role in controlling the excitability and responsiveness of cortical neurons. Present study analysed effects of insulin induced hypoglycemia and streptozotocin induced diabetes on the cortical GABA receptor binding, GABA(Aά1), GABA(B) receptor subtype expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This is the evidence that hypoglycemia amplifies the adverse effects of hyperglycemia on GABAergic system, and the impairments of functions of GABAergic neurons in the diabetic cerebral cortex are intensified in hypoglycemia. The expression of glutamate decarboxylase, the rate-limiting enzyme of GABA synthesis, which is used as a marker of GABAergic activity, was also significantly down regulated in DM and hypoglycemia exacerbated the altered expression (Antony et al, 2010a). The same picture is found in the cerebellum, where GABA receptors are involved in control of coordination and motor learning and, like in the cerebral cortex, play a critical role in neuronal excitability and modulation of synaptic neurotransmission (Luján, 2007).…”
Section: Gaba Signalingmentioning
confidence: 91%
See 2 more Smart Citations
“…This is the evidence that hypoglycemia amplifies the adverse effects of hyperglycemia on GABAergic system, and the impairments of functions of GABAergic neurons in the diabetic cerebral cortex are intensified in hypoglycemia. The expression of glutamate decarboxylase, the rate-limiting enzyme of GABA synthesis, which is used as a marker of GABAergic activity, was also significantly down regulated in DM and hypoglycemia exacerbated the altered expression (Antony et al, 2010a). The same picture is found in the cerebellum, where GABA receptors are involved in control of coordination and motor learning and, like in the cerebral cortex, play a critical role in neuronal excitability and modulation of synaptic neurotransmission (Luján, 2007).…”
Section: Gaba Signalingmentioning
confidence: 91%
“…The various neurotransmitter systems, including dopaminergic, serotonergic, cholinergic, glutamatergic, and GABAergic, undergo a significant change in DM (Jackson & Paulose, 1999;Gireesh et al, 2008;Antony et al, 2010a;Anu et al, 2010; T.P. Kumar et al, 2010) (Fig.…”
Section: Neurotransmitter Signaling Systems In the Diabetic Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some studies showed increases in extracellular GABA concentrations (Ohtani et al, 1997;Chan et al, 2011), whereas others did not (Guyot et al, 2001). Moreover, it has been reported that in control rats but not in diabetic animals, GABA levels are increased after stress (Gomez et al, 2003), whereas the number of GABA receptors is decreased (Antony et al,. 2010;Sherin et al,.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the selective vulnerability of the corpus callosum, and specifically, the subgroups of callosal projection neurons, experimental studies suggest the combined role of excitotoxicity as well as glucose starvation in the pathogenesis of hypoglycemic brain injury [11]. For example, in rat models, hypoglycemia decreases GABAergic neuroprotective function and increased vulnerability of the cerebral cortex to neuronal damage [12]. Cortical projection neurons have discrete intrinsic membrane properties, bursting behavior, and spontaneous spike frequencies as compared to other cortical neurons.…”
Section: Possible Mechanisms For Symmetric Cortical Injurymentioning
confidence: 99%